1993
DOI: 10.1111/j.1365-2249.1993.tb06000.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of antiphospholipid antibody by ELISA using purified β2-glycoprotein I in preeclampsia

Abstract: SUMMARYIt has been reported tiiat the binding of some antiphospholipid antibodies (APA) to phospholipids requires llic presence of /frglycoprotein I (/(:-GPI), Using a new ELISA. in which well coaled phosphoiipids were treated witiiaeonstantamount of"puriiied/^-GPI. we tried to detect liie presence of APA which binds lo phosphoiipid//^;-GPI eomplex or to phospholipids sueh as eardioiipin (CA) and phnsphittidylserine (PS) in preeeiampsia. and to check for cliniciii abnormaiilies in iintibodypositivc eases. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In other words, the relationship between hypertension, cerebral hemorrhage and infarction is complex. Furthermore, studies have suggested immune system involvement in pregnancy hypertension [38][39][40][41], but not in essential hypertension.…”
Section: Pih Susceptibility Genesmentioning
confidence: 99%
“…In other words, the relationship between hypertension, cerebral hemorrhage and infarction is complex. Furthermore, studies have suggested immune system involvement in pregnancy hypertension [38][39][40][41], but not in essential hypertension.…”
Section: Pih Susceptibility Genesmentioning
confidence: 99%
“…Besides the cellular abnormalities already discussed, autoantibody abnormalities have also been reported in association with preeclampsia. So far, a number of autoantibodies have been implicated in the pathogenesis (Branch et al, 1994;Milliez et al, 1990;Rappaport et al, 1990;Yamamoto et al, 1993). The most important one of them appears to be an agonistic autoantibody against the angiotensin II type 1 receptor (Wallukat et al, 1999).…”
Section: The Association Between Preeclampsia and Autoimmunitymentioning
confidence: 99%
“…Moreover, as in classical autoimmune diseases, more severe preeclampsia appears to result in more autoantibody abnormalities (El-Roeiy et al, 1991). Evidence suggests that classical, nonorgan-specific autoantibodies, such as antiphospholipid antibodies, are characteristic of preeclampsia, and especially in its more severe clinical expression (El-Roeiy et al, 1991;Yamamoto et al, 1993). Dekker et al therefore recommended active laboratory surveillance for patients at risk (Dekker et al, 1995).…”
Section: The Association Between Preeclampsia and Autoimmunitymentioning
confidence: 99%
“…Investigators have reported an increased rate of aPL in women with both preeclampsia [13,[18][19][20][21] and severe preeclampsia [20,[22][23][24]. Specifically, aCL antibodies have been reported in 11% to 29% of pregnancies complicated by preeclampsia, with pregnant control rates ranging from 0% to 7% [19,21,23,24]. Antiphospholipid antibodies are most likely to be present in patients with early-onset (before 34 weeks gestation) severe preeclampsia [22].…”
Section: Case-control Studiesmentioning
confidence: 99%